Evaluating Indonesian Consumer perceptions of H&M's Eco-Friendly campaign: The mediating role of perceived quality - Immanuel Dwi Asmoro Tunggal; Muhammad Thoyib Amali (COMMICAST, 2026)
The growing number of green products has sparked academic and practical interest in the perceived value of green products. Because of the growing number of people concerned about environmental issues, green perceived value plays an important role in brand attitude. However, perceived green value cannot be a single variable that explains brand attitude, since consumers in developing countries are inconsistent in their purchase of green products. There must be another variable. This study aims to explore the effects of green perceived value and brand prestige on brand attitude, with perceived quality as a mediator. This study uses a survey method with 200 samples across Jakarta, Bandung, Yogyakarta, and Surabaya. To test the hypothesis, this study uses Smart PLS to obtain the results. The finding is that perceived quality plays an important role in shaping brand attitude. Perceived quality could also fully mediate the relationship between Green perceived value and brand prestige toward brand attitude. The contribution of this research is to remind companies to improve their marketing communications to develop perceived quality.